Preparation of Ag/Au bimetallic nanostructures and their application in surface‐enhanced fluorescence. (18th February 2015) - Dong, Jun; Ye, Yanyan; Zhang, Wenhui; Ren, Zebin; Huo, Yiping; Zheng, Hairong
Abstract: An effective substrate for surface‐enhanced fluorescence, which consists of cluster Ag/Au bimetallic nanostructures on a copper surface, was synthesized via a multi‐stage galvanic replacement reaction of a Ag cluster in a chlorauric acid (HAuCl4 ) solution at room temperature. The fabricated silver/gold bimetallic cluster were found to yield large surface‐enhanced fluorescence (SEF) enhancement factors for rhodamine 6G probe molecules deposited on the substrate, and also the fluorescence efficiency is critically dependent on the period of nanostructure growth. With the help of proper control reaction conditions, such as the reaction time, and concentration of reaction solutions, the maximum fluorescence enhanced effect was obtained. Therefore, the bimetallic nanostructure substrate also can be adapted to studies in SEF, which will expand the application of SEF. Copyright © 2015 John Wiley & Sons, Ltd.